Peningkatan Hasil Belajar Menulis Recoun Text pada Siswa Kelas Viiig Melalui Model Pembelajaran Problem-Based Learning di SMP Negeri 1 Sambungmacan - Imaya Wijayanti; Arin Arianti; Atika Hernian Asri (Syntax Idea)
This research aims to enhance the learning outcomes of recount text writing for kelas VIIIG SMP Negeri 1 Sambungmacan in the academic year 2023—2024 through the implementation of the problem-based learning instructional model. The objectives of this research are (a) to ascertain the effectiveness of the problem-based learning model in improving the ability to write recount texts, (b) to understand the process of students' learning outcomes improvement, and (c) to determine the extent of the improvement in recount text writing skills for eighth-grade students at SMP Negeri 1 Sambungmacan in the academic year 2023—2024 before and after the implementation of the problem-based learning model. This study follows a Classroom Action Research (CAR) design, conducted over two cycles, each involving four stages: planning, implementation, observation, and reflection. The research subjects are 30 students kelas VIIIG at SMP Negeri 1 Sambungmacan in the academic year 2023—2024. Both quantitative and qualitative analyses were employed for data analysis. The results of the analysis indicate an improvement in recount text writing learning outcomes in the first cycle with the topic of "unforgettable experiences," where the average score was 73.53, falling into the less satisfactory category. However, in the same material in the second cycle, the average score increased to 84.03. Based on these findings, it is concluded that the problem-based learning model is suitable for enhancing students' learning outcomes in recount text writing with the topic of "unforgettable experiences." Moreover, the problem-based learning model can be applied to other English language topics and across various subjects.